Holistic Care for Reducing Pain Intensity among Individual with Rheumatoid Arthritis: A Systematic Literature Review - Nurazizah, Tsaniya; Naurah, Ghina Nurjihan; Oktaviani, Shopia; Hidayat, Nur; Setiawan, Henri; Kusumawaty, Jajuk; Suhanda, Suhanda (Inspirasi Foundation, 2026)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disorder marked by persistent joint inflammation that causes pain, stiffness, and impaired mobility. While pharmacological treatment helps manage symptoms, some patients experience side effects or inadequate pain control. Therefore, holistic approaches involving psychological, lifestyle, and physical therapies are increasingly considered to support overall well-being and complement medical management. Objective: This systematic review aims to assess the effectiveness of holistic interventions in reducing pain intensity among individuals with RA. Method: A systematic search of six databases PubMed, ProQuest, Garuda, JSTOR, ScienceDirect, and Wiley was conducted for studies published between 2020 and 2024. Eligible studies included RA patients whose pain intensity was measured using validated tools such as the Numerical Rating Scale (NRS), Visual Analog Scale (VAS), or McGill Pain Questionnaire (MPQ). Two independent reviewers performed study selection and data extraction, while quality assessment followed PRISMA guidelines and the CASP Checklist. Results: Eleven studies comprising 607 participants met the inclusion criteria. The findings showed that holistic interventions including warm ginger compresses, Swedish massage, hand and foot massage, lavender aromatherapy, eucalyptus inhalation, Reiki therapy, and combined ginger compress with rheumatic exercise, were effective in reducing pain intensity in RA patients. Most studies reported significant improvements, with warm ginger compress being the most consistently effective method across various settings. Conclusion: Holistic approaches demonstrate meaningful benefits in reducing pain and supporting comfort in individuals with RA, particularly among older adults. Consistent application and appropriate duration of therapy enhance effectiveness. Overall, holistic care serves as a valuable complementary strategy that promotes patient-centered pain management and improves quality of life.